(untitled) (Bangladesh Agronomy Journal, 2015)
A trial was conducted at the FSRD site, Elenga and MLT site, Ghatail, Tangail during 2011-12 and 2012-13 to test the performance of the BARI developed USG applicator in boro rice and to find out the economic performance of the USG applicator in the farmers field. The BARI developed USG applicator was tested against the USG application by hand and the conventional method of granular urea application. The average higher grain yield (7.05 t ha-1 and 7.07 t ha-1) of two years were obtained from the plot of USG application with BARI applicator in the both locations, respectively The highest gross return (120410 Tk. ha-1 & 20290 Tk. ha-1) and gross margin (64346 Tk. ha-1 and 62164 Tk. ha-1) during 1011-12 and 2012-13 were obtained from the plots treated with USG by BARI applicator at the FSRD site Elenga and MLT site Ghatail, respectively. Field efficiency of BARI USG applicator and hand application was 0.12 hah-1 and 0.027 hah-1, respectively. BARI USG applicator saved time 77.65% compared to that of hand application of USG in boro rice field. It also saved labor cost against the USG application by hand and reduces 33% urea over the granular urea application in conventional method. Bangladesh Agron. J. 2014, 17(2): 77-81